2023
DOI: 10.1109/ojcoms.2023.3239434
|View full text |Cite
|
Sign up to set email alerts
|

Proactively Predicting Dynamic 6G Link Blockages Using LiDAR and In-Band Signatures

Abstract: Line-of-sight link blockages represent a key challenge for the reliability and latency of millimeter wave (mmWave) and terahertz (THz) communication networks. To address this challenge, this paper leverages mmWave and LiDAR sensory data to provide awareness about the communication environment and proactively predict dynamic link blockages before they occur. This allows the network to make proactive decisions for hand-off/beam switching, enhancing the network reliability and latency. More specifically, this pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 30 publications
2
3
0
Order By: Relevance
“…However, this approach requires dynamic cooperation between UEs in real-time, which might not be feasible in practice. Finally, the authors in [10], [11] observed the so-called "pre-blockage signatures" that occurred in mmWave/sub-THz channel before blockage events, which we also observed in our experiments. Subsequently, by operating in the time domain they utilized a recurrent neural networks for the proactive detection of blockage events.…”
Section: Introductionsupporting
confidence: 85%
See 3 more Smart Citations
“…However, this approach requires dynamic cooperation between UEs in real-time, which might not be feasible in practice. Finally, the authors in [10], [11] observed the so-called "pre-blockage signatures" that occurred in mmWave/sub-THz channel before blockage events, which we also observed in our experiments. Subsequently, by operating in the time domain they utilized a recurrent neural networks for the proactive detection of blockage events.…”
Section: Introductionsupporting
confidence: 85%
“…They last for approximately 100-200 ms which is sufficiently long not only to detect the blockage before it occurs but also to take actions to avoid it, e.g., reroute the active session to the back-up link by utilizing the multiconnectivity functionality [5], [12]. We also note that similar behavior was reported in [10], [11] for mmWave band.…”
Section: B Main Hypothesissupporting
confidence: 66%
See 2 more Smart Citations
“…This study is primarily concerned with predicting the timing of LoS link blockage, a task that can be accomplished by knowing the range and height of an object. While comprehensive object dimensions, such as length and width, are of lesser importance for this purpose, they will become crucial for estimating the duration of link blockages [27]. Investigating these full object dimensions represents a potential area of research expansion in the future, building upon this work.…”
Section: A Overview and Schematic Diagrammentioning
confidence: 96%